2021
DOI: 10.2308/jata-18-055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prefilled Tax Returns on Taxpayer Compliance

Abstract: This study uses two online experiments to examine the potential consequences of a recent U.S. Senate proposal to prefill federal income tax returns on behalf of individuals. Consistent with omission theory, we find that prefilled returns lower compliance compared to selfcompleted returns when the prefilled returns do not estimate undocumented income (e.g., cash tips). However, the results show that including estimates of undocumented income increases taxpayer compliance relative to self-completed returns. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Nevertheless, student compliance greatly improved by introducing the option to pre-populate tax returns (infrequent pre-filled reporting) with a relatively small economic cost. This finding aligns with the recent literature on the effectiveness of pre-populated tax returns on compliance (Doxey et al, 2021;Fochmann et al, 2021;van Dijk et al, 2020); that is, pre-filled tax returns can increase compliance, particularly if they are pre-populated correctly and accurately.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, student compliance greatly improved by introducing the option to pre-populate tax returns (infrequent pre-filled reporting) with a relatively small economic cost. This finding aligns with the recent literature on the effectiveness of pre-populated tax returns on compliance (Doxey et al, 2021;Fochmann et al, 2021;van Dijk et al, 2020); that is, pre-filled tax returns can increase compliance, particularly if they are pre-populated correctly and accurately.…”
Section: Discussionsupporting
confidence: 89%
“…The use of pre-populated tax returns is expected to increase the compliance of taxpayers, through the removal of self-reporting-based errors. Several studies show that the average level of compliance is higher for pre-filled returns (Doxey et al, 2021;Fochmann et al, 2021;van Dijk et al, 2020). The caveat, however, is that compliance for pre-filled is only higher when the undocumented income is included, or when the estimated income level is correct or greater than the actual income (Doxey et al, 2021;Fochmann et al, 2021;van Dijk et al, 2020).…”
Section: Infrequent Pre-filled Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-filled tax return is a tax declaration that a tax administration prepares for a taxpayer using information provided by the taxpayer and information from third-party sources, such as banks and employers. The pre-filling of tax returns was first implemented in Denmark in the late 1980s (Doxey, Lawson, and Stinson 2021). Later the policy was adopted in several countries, including some tax jurisdictions in Latin America and the Caribbean.…”
Section: Pre-filled Tax Returnsmentioning
confidence: 99%
“…Another study in Denmark found that pre-filling deductions in tax returns is associated with an increase in the number of tax deductions claimed by 100 percent, and in the value of tax deductions claimed by 15 percent (Gillitzer and Skov 2018). The pre-filling of tax returns was also evaluated in several laboratory experiments, yielding inconclusive evidence of their impact (Bruner et al 2015;Fonseca and Grimshaw 2017;van Dijk et al 2020;Doxey, Lawson, and Stinson 2021;Fochmann, Müller, and Overesch 2021). In the context of Latin America and the Caribbean, a report by the Economic Commission for Latin America and the Caribbean notes that pre-filling value-added tax returns in Ecuador reduced compliance time from 30 to 6 minutes per taxpayer for each value-added-tax return (Gonzalez, Romero, and Padilla 2019).…”
Section: Pre-filled Tax Returnsmentioning
confidence: 99%